(untitled) (Acta Scientiarum. Biological Sciences, 2022)
Mulching use in agriculture has been known since 1802 as the practice of spreading dry leaves and straw on the soil to prevent erosion and water loss. Our study evaluated the mulch effectiveness in the establishment of regenerating seedlings and its contribution to the control of exotic grasses. The studies were carried out in an ecological restoration area in the municipality of Itapira-SP. The treatment with mulching consisted in chemical desiccation with glyphosate herbicide application, keeping the dry grass on the ground. In the control treatment, after chemical weeding, the grass was removed with manual mowing, exposing the soil. Eight months after implantation, we sampled all regenerating seedlings in 100 plots of 50 x 50 cm in each treatment. We considered as seedlings all individuals of tree species less than 100 cm tall. We calculated richness, abundance, similarity, and the relationship of the frequency of seedlings to the height of the mulch. We sampled eight species with 42 seedlings, with only one not identified. The highest abundance and species richness were found in the treatment with mulch (n = 34 individuals; eight species), the most abundant being Schinus terebinthifolia Raddi (14 individuals) followed by Solanum mauritianum Scop. (11 individuals), and Platypodium elegans Vog. (three individuals). The presence of exotic grasses was lower in the plots of the mulching (13%) compared to the control treatment (67%). The highest frequency of seedlings was obtained with mulch height from 21 to 37 cm. We suggest that adaptive management practices, such as the use of the mulching technique, can be implemented in ecological restoration areas, because they favor the natural regeneration of native seedlings and can contribute to the control of exotic grasses, but the height of the layer must be controlled.